2022
DOI: 10.3390/microplastics1020016
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Microplastics by Pyrolysis Coupled with Gas Chromatography and Mass Spectrometry in Sediments: Challenges and Implications

Abstract: Pyrolysis-GC/MS is increasingly used to quantify microplastics (MP) in environmental samples. In general, prior to analysis, purification steps are carried out to reduce the environmental matrix in sediment samples. The conventionally used protocol of density separation followed by digestion of organic matter does not allow for complete isolation of MP from the associated organic and mineral matter. Among the pyrolysis products used as indicator compounds for plastic polymers, some may originate from other sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…We observed that none of the chlorinated substances and plant components had an interfering effect on the C-IC measurement, and therefore, no influence on the analysis of PVC was observed. Thus, this method is selective for chlorine-containing polymers and is not limited by matrix effects known for other thermoanalytical methods. ,,,,, …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We observed that none of the chlorinated substances and plant components had an interfering effect on the C-IC measurement, and therefore, no influence on the analysis of PVC was observed. Thus, this method is selective for chlorine-containing polymers and is not limited by matrix effects known for other thermoanalytical methods. ,,,,, …”
Section: Resultsmentioning
confidence: 99%
“…Thus, this method is selective for chlorine-containing polymers and is not limited by matrix effects known for other thermoanalytical methods. 6 , 19 , 24 , 25 , 27 , 28 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some studies reported methods of analysis of MPs using PY-GC/MS without the pre-treatment step (filtration or oxidative processes), the organic matter can still interfere. 114,121 Compared to other thermal analytical methods presented here, Py-GC/MS is the least affected by the organic matter. However, the amount of organic matter contained in the sample will determine if any pre-treatment is needed.…”
Section: Thermal Analytical Methodsmentioning
confidence: 95%
“…117–119 However, Py-GC/MS limitations are sample destruction, the inability to detect inorganic additives and suffering from the interference of the residual organic matter and mineral matrix, particularly for sediment samples. 114…”
Section: Thermal Analytical Methodsmentioning
confidence: 99%